Hexad-12: Developing and Validating a Short Version of the Gamification User Types Hexad Scale - Krath, Jeanine; Altmeyer, Maximilian; Tondello, Gustavo F.; Nacke, Lennart E. (Conference on Human Factors in Computing Systems - Proceedings, 2023)
The Hexad scale is a crucial tool for personalized gamification in user experience (UX) design. However, completing a 24-item questionnaire can increase dropout rates and screen fatigue within online surveys. When included in larger surveys, scale brevity makes a difference. To reduce the time required for the assessment process, we developed and validated a 12-item version of the Hexad scale. To create it, we carried out an exploratory factor analysis on an existing data set to identify appropriate items (n = 882). To validate the 12-item version, we conducted a confirmatory factor analysis on a new data set (n = 1, 101). Our results show that Hexad-12 outperforms the original Hexad scale regarding model fit, reliability, convergent, and discriminant validity. Therefore, Hexad-12 resolves issues found in studies using the original Hexad scale and provides a suitable and swift instrument for concisely assessing Hexad user types in tailored gamification design.
Created from Fastlane, Scopus look-up
Keywords: Adaptive Gamification; Gamification; Hexad; Personalization; Player Types; Tailored Gamification; User Types